Britannia and Eve : a Monthly Journal for Men & Women (voortzetting van Eve (1926) en Britannia (1928)). (Londen, 1929)
Britannia and Eve first appeared in 1926 as Eve, a self-described ‘Lady’s Pictorial’, while Britannia was printed throughout 1928. Eventually, on May 1st 1929, the two newspaper combined to become Britannia and Eve with the new tagline ‘A Monthly Journal for Men & Women’. Each incarnation was printed in London (British Newspaper Archive)
Online: https://www.britishnewspaperarchive.co.uk/titles/britannia-and-eve
Engels
Tijdschriften